ASSESSMENT OF DIGITAL TERRAIN MODELS IN DAM BREAK SIMULATION STUDIES - Lima, Rodrigo Pereira; Elmiro, Marcos Antonio Timbó; Nero, Marcelo Antonio; Temba, Plínio da Costa; Fonseca, Bráulio Magalhães; Castiglione, Luiz Henrique Guimarães (Boletim de Ciências Geodésicas, 2022)
Dams are structures built for controlling the flow of water for many useful purposes such as water supply, power generation, retention of mining and industrial waste, as well as recreation and flood control. However, they bring together some risk of dam body collapse causing damage for the dam downstream areas. Therefore, hypothetical dam break studies which provide mapping of areas potentially attainable in the event of a rupture are especially important for planning actions aiming minimization of associated losses. The aim of this research is to assess the degree of adherence or similarity between flood maps obtained by simulation studies and those effectively obtained from the collapse itself occurred in Dam I owned by Vale SA on January 25, 2019. The study focuses mainly on comparing the effects over the simulated flood maps caused by use of different representation of dam downstream topography relief, namely Shuttle Radar Topography Mission (SRTM), Advanced Land Observing Satellite from Alaska Satellite Facility (ALOS_ASF) and Airborne Laser Scanning (ALS) models. The simulations were performed using the HEC-RAS software developed by the US Army Corps of Engineers considering hypothesis of strong influence of relief in flood mapping results. In this way, three simulation tests were carried out for evaluation and discussion. In the first simulation, the digital terrain model derived from ALS was used. The second simulation was carried out associating the digital surface model ALOS_ASF with a spatial resolution of 12.5 m. Finally, the SRTM digital elevation model with 30 m spatial resolution provided by the United States Geological Survey (USGS) was used in third simulation. Results showed better adherence to simulations using data from ALS. This was verified by visual analysis over high resolution orthorectified images and by calculating statistics indicators such as the (F) index. Conclusions pointed out that flood patches resulting from simulation are critical tools for taking actions involving areas and populations to be affected, so the best relief model technologies like ALS data should be used in simulation.